2016
DOI: 10.1007/s00011-016-0967-5
|View full text |Cite
|
Sign up to set email alerts
|

GM-CSF and GM-CSF receptor have regulatory role in transforming rat mesenteric mesothelial cells into macrophage-like cells

Abstract: Mesothelial cells can differentiate into macrophage-like cells, and GM-CSF, produced by the mesothelial cells, has probably an autocrine regulatory role in this transition. Our results provide new data about the plasticity of mesothelial cell and support the idea that during inflammation macrophages can derive from non-hematopoietic sources as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Far from being static actors, they are supposed to play a dynamic role in homeostasis and immunoregulation by synthesizing and secreting immune mediator-like factors [14]. Furthermore, it has been proposed, based on animal models, that under inflammatory stimuli, mesothelial cells can express macrophage markers and possibly transdifferentiate into phago-cytic macrophage-like cells [15,16]. The extensive emperipolesis of malignant lymphoid T cells by mesothelial cells seems to support this preclinical evidence in our case.…”
Section: Discussionsupporting
confidence: 71%
“…Far from being static actors, they are supposed to play a dynamic role in homeostasis and immunoregulation by synthesizing and secreting immune mediator-like factors [14]. Furthermore, it has been proposed, based on animal models, that under inflammatory stimuli, mesothelial cells can express macrophage markers and possibly transdifferentiate into phago-cytic macrophage-like cells [15,16]. The extensive emperipolesis of malignant lymphoid T cells by mesothelial cells seems to support this preclinical evidence in our case.…”
Section: Discussionsupporting
confidence: 71%
“…Granulocyte-macrophage colony-stimulating factor (GM-CSF) was once reported being able to change mesothelial cells into macrophage-like cells by an autocrine pattern [ 77 ]. GM-CSF gene expression was also associated with macrophage densities in the arterial wall [ 78 ].…”
Section: Immune Cell Infiltration In Aaamentioning
confidence: 99%
“…We found that during inflammation-induced EMT mesenteric mesothelial cells start to express macrophage markers (OX43, ED1) as well [1,13]This observation raised the possibility that mesothelial cells might transdifferentiate into macrophage-like cells [14]. This idea seemed to be even more likely since our previous data showed that under inflammatory stimuli the number of macrophages appearing in the peritoneal cavity dramatically increased [15].…”
Section: Inflammation Induced Emt Transdifferentiates Mesothelial Celmentioning
confidence: 60%